2016
DOI: 10.3390/rel7010011
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Prayer on Patients’ Health: Systematic Literature Review

Abstract: Abstract:There is increasing interest regarding prayer in healthcare. Prayer is an activity related to spirituality and religion. Positive outcomes have been identified regarding spirituality in health. This study aims to investigate the effects on patients' health of using prayer. A systematic literature review was conducted in May 2015 and updated in November 2015. Electronic and international databases were searched and the inclusion criteria were based on PICOS: (Population) patients of any age and any cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 30 publications
2
34
0
3
Order By: Relevance
“…Overcoming spiritual distress was often achieved by a positive approach, proactiveness, acceptance, emotional strategies and religious strategies, which are core strategies of coping. For example, prayer was considered a religious practice closely related to spirituality that exercised a positive influence on individuals’ health and well‐being (Simão, Caldeira, & Carvalho, ). Moreover, in this study, prayer was reported in the narratives of the participants and is considered an important aid in the adjustment to being childless, to regaining hope and feeling empowered by connecting with a higher power (Batool & Visser, ; Benasutti, ; Mogobe, ; Mosalanejad et al., ; Roudsari & Allan, ; Toscano & Montgomery, ).…”
Section: Discussionmentioning
confidence: 99%
“…Overcoming spiritual distress was often achieved by a positive approach, proactiveness, acceptance, emotional strategies and religious strategies, which are core strategies of coping. For example, prayer was considered a religious practice closely related to spirituality that exercised a positive influence on individuals’ health and well‐being (Simão, Caldeira, & Carvalho, ). Moreover, in this study, prayer was reported in the narratives of the participants and is considered an important aid in the adjustment to being childless, to regaining hope and feeling empowered by connecting with a higher power (Batool & Visser, ; Benasutti, ; Mogobe, ; Mosalanejad et al., ; Roudsari & Allan, ; Toscano & Montgomery, ).…”
Section: Discussionmentioning
confidence: 99%
“…This domain introduced the need to expand scientific knowledge, in terms of recognizing the spiritual needs of both patients and the population at large. Thus, aspects that transcend the human dimension, which include cosmic structures higher than those imposed by the material world, reinforce mechanisms that enhance how humans interact with others and the world (5) . The spiritual domain refers to the search for meaning and answers to fundamental aspects of life through experiences with the sacred and transcendent, which can improve health conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Current anthropological studies have shown that religious views are still present in all social strata as an important part of how health and illness processes are understood (2) , and a growing number of health studies have been conducted on the topic, especially among the older adult population (3)(4) . As described by Simão, Caldeira, and Carvalho (5) , important paradigmatic shifts, such as the consideration of nonmaterial or spiritual dimensions, compose the concept of health. In the last century, the World Health Organization created the Quality of Life Group, which touches on the domains of spirituality/religion/ personal beliefs in its global instrument to assess quality of life (QOL) (6) .…”
Section: Introductionmentioning
confidence: 99%
“…Prayer is regarded as an intervention and a way of attending to the person's spiritual needs, in the context of nursing (14) . Therefore, this intervention should be part of the activities carried out by health professionals, especially nurses, during the performance of their habitual practices, in order to provide advantages to conventional treatment and attend to the patients' spirituality (13) . According to the results of the study (13) , using prayer in clinical practice can provide multiple beneficial effects, such as reduction of mortality in patients with bloodstream infections, reduction of anxiety, and depression and better physical functioning.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, professionals involved in health care should be encouraged to take actions in the spiritual realm, such as prayer, during the process of coping with illness (12) , bearing in mind that the care provided to the patients should follow a holistic approach, meaning that all the patients' needs should be addressed, as it is often established in professional codes of ethics and health policies (13) . Prayer is regarded as an intervention and a way of attending to the person's spiritual needs, in the context of nursing (14) .…”
Section: Introductionmentioning
confidence: 99%